2004
DOI: 10.2458/azu_jrm_v57i6_johnson-nistler
|View full text |Cite
|
Sign up to set email alerts
|

Black-Tailed Prairie Dog Effects on Montana's Mixed-Grass Prairie

Abstract: Forty paired sites were examined on the mixed-grass prairie of northeastern Montana to compare the effects of black tailed prairie dog (Cynomys ludovicianus) colonies on native range vegetation. Thirty 0.25-m2 quadrats were placed on colonized and uncolonized locations and matched by environmental conditions. Cover and standing crop biomass of each plant species was estimated using a double sampling procedure where every third plot was clipped and estimated. A total of 2 400 quadrats were estimated, whereas 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Forbs, bare ground and purple threeawn are more abundant on prairie dog colonies, but both noncolonized and colonized areas are dominated by a warm-season shortgrass, blue grama (Winter et al 2002). In contrast, the Phillips County landscape includes greater topographic variability, a diversity of soil types, and off-colony vegetation with tallerstructure, cool-season grasses and sagebrush (Reading and Matchett 1997;Johnson-Nistler et al 2004). These differences, especially the difference in vegetation structure, likely aid prairie dog colonization or expansion into unoccupied grassland on Comanche compared to Phillips County.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forbs, bare ground and purple threeawn are more abundant on prairie dog colonies, but both noncolonized and colonized areas are dominated by a warm-season shortgrass, blue grama (Winter et al 2002). In contrast, the Phillips County landscape includes greater topographic variability, a diversity of soil types, and off-colony vegetation with tallerstructure, cool-season grasses and sagebrush (Reading and Matchett 1997;Johnson-Nistler et al 2004). These differences, especially the difference in vegetation structure, likely aid prairie dog colonization or expansion into unoccupied grassland on Comanche compared to Phillips County.…”
Section: Discussionmentioning
confidence: 99%
“…Grassland areas are dominated by western wheatgrass (Pascopyrum smithii), blue grama, needle-and-thread (Hesperostipa comata) and green needlegrass (Stipa viridula), and shrub-dominated areas contain big sagebrush (Artemesia tridentata) and greasewood (Sarcobatus vermiculatus) (Reading and Matchett 1997). Vegetation of non-colonized grassland has substantially greater abundance of cool-season perennial grasses (western wheatgrass and needle-andthread) and sagebrush than areas colonized by prairie dogs (Johnson-Nistler et al 2004). The area is grazed by cattle, typically during May-October, at stocking rates of approximately 2-3 ha/AUM.…”
Section: Comanche National Grassland Coloradomentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that prairie dogs substantially reduced the standing biomass and increased the protein content of plants growing on colonies, but did not assess effects on forage digestibility. More recently, Johnson-Nistler et al (2004) measured forage quantity, protein content, and digestibility at a complex of prairie dog colonies in the north mixed prairie of Montana. Prairie dogs reduced standing herbage by 62% (from 32 g/m 2 off colonies to 12 g/m 2 on colonies), while increasing the weighted-average N content of herbage from 1.28% to 1.73% (36% relative increase) and the weighted-average in vitro dry matter digestibility to a lesser degree, from 32.3% to 36.2% (12% relative increase; not statistically significant).…”
Section: Introductionmentioning
confidence: 99%
“…We quantified spatiotemporal variation in forage quantity and quality at three prairie dog colony complexes in the western Great Plains (Fig. 1), and obtained additional data on forage quality and quantity from a fourth complex (Johnson-Nistler et al 2004). Our objectives were to assess (1) spatial variation in the trade-offs between forage quantity and quality among prairie dog colony complexes located in the northern mixed prairie (dominated by a mixture of mid-height, C 3 and short, C 4 perennial grass species) vs. the shortgrass steppe (dominated by short, C 4 perennial grasses), (2) temporal variation in forage quality/quantity trade-offs among years, related to above-and below-average precipitation conditions, and (3) temporal variation in forage quality/ quantity trade-offs over the growing season at each complex.…”
Section: Introductionmentioning
confidence: 99%